The Video Head Impulse Test - Halmagyi, G. M.; Chen, Luke; MacDougall, Hamish G.; Weber, Konrad P.; McGarvie, Leigh A.; Curthoys, Ian S. (Frontiers in Neurology, 2017)
In 1988 we introduced impulsive testing of semicircular canal function measured with scleral search coils and showed that it could accurately and reliably detect impaired function even of a single lateral canal. Later we showed that it was also possible to test individual vertical canal function in peripheral and also in central vestibular disorders, and proposed a physiological mechanism for why this might be so. For the next 20 years, between 1988 and 2008, impulsive testing of individual semicircular canal function could only be accurately done by a few aficionados with the time and money to support scleral search coil systems – an expensive, complicated and cumbersome, semi-invasive technique that never made the transition from the research lab to the dizzy clinic. Then in 2009 and 2013 we introduced a video method of testing function of each of the 6 canals individually. Since 2009 the method has been taken up by most dizzy clinics around the world, with now close to 100 refereed articles in PubMed. In many dizzy clinics around the world video Head Impulse Testing has supplanted caloric testing as the initial and in some cases the final test of choice in patients with suspected vestibular disorders. Here we consider 7 current, interesting and controversial aspects of video Head Impulse Testing: 1. Introduction to the test; 2. the progress from the head impulse protocol (HIMPs) to the new variant – suppression head impulse protocol (SHIMPs); 3. The physiological basis for head impulse testing; 4. Practical aspects and potential pitfalls of video Head Impulse Testing; 5. Problems of vestibulo-ocular reflex gain calculations; 6. Head impulse testing in central vestibular disorders, and 7. To stay right up-to-date – new clinical disease patterns emerging from video head impulse testing. With thanks and appreciation we dedicate this article to our friend, colleague and mentor, Dr Bernard Cohen of Mount Sinai Medical School, New York, who since his first article 55 years ago on compensatory eye movements induced by vertical semicircular canal stimulation, has become one of the giants of the vestibular world.